2005
DOI: 10.1007/s11738-005-0062-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant Ca2+-ATPases

Abstract: Plant Phys i ol ogy De part ment, In sti tute of Plant Bi ol ogy, Wrocław Uni ver sity, Ab stractPlant cal cium pumps, sim i larly to an i mal Ca 2+ pumps, be long to the superfamily of P-type ATPases com pris ing also the plasma mem brane H + -ATPase of fungi and plants, Na + /K + ATPase of an i mals and H + /K + ATPase of mam ma lian gas tric mu cosa. Ac cord ing to their sen si tiv ity to calmodulin the plant Ca 2+ -ATPases have been di vided into two sub groups: type IIA (homo logues of an i mal SERCA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 87 publications
0
22
0
Order By: Relevance
“…ATPases family in Arabidopsis. This family encompasses ten members and only few have been characterized at the functional level (Kabała and Kłobus 2005;Boursiac and Harper 2007). Protein sequence analysis showed that ACA7 presented the characteristic domains conserved across the ACA family, including the N-terminal calmodulin sensor domain that regulates the activity of this family of Ca 2?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ATPases family in Arabidopsis. This family encompasses ten members and only few have been characterized at the functional level (Kabała and Kłobus 2005;Boursiac and Harper 2007). Protein sequence analysis showed that ACA7 presented the characteristic domains conserved across the ACA family, including the N-terminal calmodulin sensor domain that regulates the activity of this family of Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…ACA proteins are part of the PIIB type of Ca 2? -ATPases, with ten members in Arabidopsis (Kabała and Kłobus 2005). They all present a calmodulin-regulated autoinhibitory domain and show nearly 50% protein sequence identity with animal plasma membrane type (PM-type) Ca 2?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previously characterized members of the ACA subgroup, the N-terminus has been found to have an auto-inhibitory domain and a partially overlapping high affinity calmodulin (CaM) binding site (Geisler et al 2000a; Baxter et al 2003; Kabala and Klobus 2005; Boursiac and Harper 2007; Bonza and De Michelis 2011; Pedersen et al 2012); a second low affinity CaM-binding site has been recently identified just 8 aa downstream the first one in ACA8, one of the best characterized ACA isoform (Tidow et al 2012). In all ACA isoforms characterized so far, CaM-binding suppresses the auto-inhibitory action of the N-terminus, increasing V max and decreasing K 0.5 for free Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…For example, ACA2 and ACA4 are located at the endoplasmic reticulum and the prevacuolar membrane, respectively, whereas ACA8 and ACA9 are located on the plasma membrane (15; reviewed in Refs. 16,17). The BCA1 protein is a type IIB Ca 2ϩ -ATPase with a vacuolar localization that was discovered in the plant Brassica oleracea (cauliflower) (18).…”
mentioning
confidence: 99%